Dichloridotetrakis(diniconazole)nickel(II) - Xiong, Zhi-Qiang (International Union of Crystallography, 2011)
In the title compound, [NiCl(2)(C(15)H(17)Cl(2)N(3)O)(4)], the Ni atom lies on an inversion center and has an axially extended trans-NiCl(2)N(4) octahedral geometry arising from its coordination by four diniconazole [systematic name: (E)-(RS)-1-(2,4-dichlorophenyl)-4,4-dimethyl-2-(1H-1,2,4-triazol-1-yl)pent-1-en-3-ol] ligands and two chloride ions. In the crystal, O—H⋯Cl hydrogen bonds link the molecules into [100] chains.